Analytical studies and design of steel plate girder ABC bridges under seismic loads. (15th January 2021) - Shoushtari, Elmira; Saiidi, M. Saiid; Itani, Ahmad; Moustafa, Mohamed A.
Highlights: Routine analytical model with nonlinear columns reasonably matches test results. Cap-to-girder moment and column axial forces are very sensitive to VGA. VGA should be considered in design and analysis of bridges in near-fault regions. Abstract: Despite the numerous advantages that accelerated bridge construction (ABC) offers over the conventional construction, some bridge officials in moderate and high seismic areas have not been sufficiently confident to embrace it extensively. This is due to the insufficient research data and guidelines for seismic design of prefabricated members and connections, as well as reliable analytical modeling methods for ABC bridges. The main objective of the current study was to address this issue through analytical investigations of a two-span steel girder bridge system with six ABC connections that was tested on shake tables at the University of Nevada, Reno. A three-dimensional finite element model was developed in OpenSEES and found to be adequate in capturing the key seismic response parameters of the bridge model. The effects of the vertical ground motions and bi-axial excitations on the seismic response of the bridge elements and connections were investigated and found that some of the response parameters can be significantly affected by near-fault earthquakes. Design methods were developed based on the results of the shake table test, previous studies on the connections, and the parametric studies. The article also presents design guidelines for column-footing rebar hinge pocket connections and column-cap beam hybrid grouted duct connections prepared based on the AASHTO format.